MEMO Organisation Modelling Language: Requirements and core diagram types - Ulrich Frank (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2011)
An enterprise model comprises various abstractions of an enterprise that represent both information systems and the surrounding action systems. These different models are integrated in order to avoid redundant work and to contribute to a tight and consistent integration of action systems and information systems. For this purpose, the method MEMO (Multi-Perspective Enterprise Modelling) features a family of modelling languages, each of which is aimed at representing specific perspectives and aspects of an enterprise. Within the MEMO languages, the Organisation Modelling Language (MEMO OrgML) is of outstanding relevance. It allows for creating elaborate models of business process types (organisational dynamics) and of organisation structures. Therefore, it is a key instrument for analysing and (re-) designing a company's action system, i.e. its key patterns of division of labour and coordination with respect to organisational goals. This report is intended to prepare for a major revision of the MEMO OrgML. Therefore, its focus on terminological foundations and on the comprehensive analysis of requirements related to the design of organisation modelling languages. The analysis was guided by a method for developing domain-specific modelling languages. It suggests focussing on use scenarios to analyse and refine requirements. The analysis is differentiated into general requirements for DSML and general as well as specific requirements for organisation modelling languages. The results are presented in an extensive dictionary of almost 70 requirements on different levels of abstraction.
Keywords: 650